Critical Thinking Education and Debiasing (AILACT Essay Prize Winner 2013) - Guillaume Beaulac; Tim Kenyon (Informal Logic, 2014)
There are empirical grounds to doubt the effectiveness of a common and intuitive approach to teaching debiasing strategies in critical thinking courses. We summarize some of the grounds before suggesting a broader taxonomy of debiasing strategies. This four-level taxonomy enables a useful diagnosis of biasing factors and situations, and illuminates more strategies for more effective bias mitigation located in the shaping of situational factors and reasoning infrastructure. The question, we contend, then becomes how best to teach the construction and use of such infrastructures.